Pengaruh Faktor Usia Ibu Hamil Terhadap Jenis Persalinan di RSUD DR. H. Abdul Moeloek Provinsi Lampung - Dwi Rani Sukma; Ratna Dewi Puspita Sari (MAJORITY, 2020)
Labor has its risks for both mother and fetus, such as illness until death risk. There is two types of labor: vaginal labor and abdominal labor. The optimal productive age for a healthy reproduction is between 20 – 35 years old. The risk will increased at the age below 20 years old and above 35 years old. This research is an quantitative research with an observational analytic design. The population of this research is the women in labor at RSUD Dr. H. Abdul Moeloek Lampung Province between July 2017 – September 2017. The sample of this research is all the women in labor between July – September 2017, in total of 191 sample. Sample is taken with purposive sampling. Research data collection was obtained from medical record. Bivariate analysis using Chi Square. The result of this research showed that pregnant women below 20 years old and above 35 years old who gave birth by vaginal labor is 52,5%. While abdominal labor is 47,5%. For pregnant woman between 20 – 35 years old who gave birth by vaginal labor is 69,7% and abdominal labor is 30,3%. The result of Chi Square analysis showed that there are effects of age factor of pregnant women and the types of labor at RSUD Dr. H. Abdul Moeloek Lampung Province with p = 0,034. OR score obtained at OR = 2,007 thus pregnant woman in risk age (below 20 and above 35 years old) has twice abdominal labor risk compared with woman with reproductive age (20-35 yearls old). There is effect of age factor of pregnant women with an type of labor at RSUD Dr. H. Abdul Moeloek Lampung Province